Nucleotide sequence of a protamine component CII gene of Salmo gairdnerii. - States, J C (1982)
We have isolated, using nick-translated cloned protamine cDNA's as probes, several genomic clones containing protamine gene sequences from a Charon 4A library of Eco R1 digested rainbow trout (Salmo gairdnerii) DNA. One clone was chosen for detailed study and the 2.5 kbp Bam HI-Eco R1 restriction fragment containing the gene was subcloned in the plasmid pBR322. A 920 bp Bg1 II - Bam HI restriction fragment contains a sequence coding for protamine component CII as well as regions 5' and 3' to the mRNA coding portion. Present in the region 5' to the mRNA coding sequence are the promoter associated signals "TATA" box and "CAAT" box. The 5' untranslated region of the mRNA whose length and sequence were not established from the cDNA clones (1) was determined by nuclease mapping and starts within a sequence similar to the "capping signal" found in other genes. The protamine gene for CII contains no introns, a situation common to most histone genes, but, unlike the histone genes does not occur close to other protamine genes in a "cluster".